Landscape characteristics in the Escondido river sub-basin, south-western Amazon, Brazil (Research, Society and Development, 2021)
The performance of agricultural activities is essential for the economic growth of society. However, it must integrate the rational use of natural resources to become sustainable. Thus, it is necessary to know the environmental conditions in the landscape to plan its management. Given the above, the objective was to carry out a detailed survey of the characteristics of the landscape in the sub-basin of the Escondido River, south-western Amazon. For that, the geometric, topographic, and hydrographic characteristics were analyzed, with the software QGIS, Google Earth, and TrackMaker Free, altimetric images from the ALOS satellite, and data from the literature. The Escondido River sub-basin has an area of 1,595.66 km2, a perimeter of 233.98 km, an elongated shape, low susceptibility to flooding, altitudes of 182 to 597 m, predominance of flat to undulating reliefs (93.69%), drainage network of 4,183.09 km, 8th order dendritic pattern, medium spring density, high drainage density, winding main channel, low maintenance coefficient and high concentration time. These characteristics show a high potential for the development of agricultural activities, however, an analysis of the soil cover dynamics is recommended, considering the topographic and hydrographic characteristics of the Escondido river sub-basin, to delimit the priority areas for conservation and recovery of native vegetation. The use of micro-basins as management subunits of the Escondido sub-basin is also recommended, as they have different landscape characteristics that influence management practices and, consequently, the efficiency of natural resource management.